Foreign teachers translanguaging beliefs and practices in English-medium classrooms at a Chinese international school - Wu, You; Othman, Juliana (Universitas Syiah Kuala, 2025)
The rise of English-medium instruction (EMI) can disadvantage students when it is limited to monolingual approaches. Translanguaging, which leverages students full linguistic repertoire, has emerged as a promising alternative. While research supports its benefits, the translanguaging practices of foreign teachers in EMI contexts remain under investigation. This case study explores foreign teachers translanguaging beliefs and practices in an international school across diverse subjects in mainland China. Focusing on a Pakistani embassy school in Beijing with a multinational student body, the study employs semi-structured interviews and classroom observations with teachers. Findings reveal mixed teacher attitudes towards translanguaging, mirroring existing research. While some embrace its potential, others demonstrate resistance, possibly due to dominant monolingual ideologies or the complex linguistic landscape. Uniquely, teachers prioritised spatial arrangements and communication strategies over students first languages (L1s) to support struggling learners. Observations and interviews suggest foreign teachers used L1s less frequently than bilingual teachers in prior studies. However, they fostered student-led translanguaging through group discussions and peer support, promoting comprehension and expression. Additionally, teachers employed various linguistic modalities during instruction yet faced inclusivity challenges due to the diverse student body. This study contributes to the under-researched area of translanguaging in EMI classrooms with foreign teachers. It highlights the varied perspectives on translanguaging and the importance of student-driven practices in such settings.